Burnout Syndrome and Coping Strategies: Basic Concepts (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2019)
The present article is a systematic review, from a bibliographic perspective, based on a selection of studies and concepts that have been part of psychology applied to sport and physical activity. Coping strategies are not frequently associated with burnout syndrome in the sports environment, despite having a close conceptual relationship that would allow considering their study as a valuable tool for developing effective training programs for its prevention. Considering that burnout syndrome has advanced in its prevalence study and that coping strategies are increasingly recognized in psychological training, the article aims to present some research advances in each of them.